Design of Highly Durable Core−Shell Catalysts by Controlling Shell Distribution Guided by In‐Situ Corrosion Study. Issue 38 (4th August 2021) - Shi, Fenglei; Peng, Jiaheng; Li, Fan; Qian, Ningkang; Shan, Hao; Tao, Peng; Song, Chengyi; Shang, Wen; Deng, Tao; Zhang, Hui; Wu, Jianbo
Abstract: Most degradations in electrocatalysis are caused by corrosion in operation, for example the corrosion of the core in a core−shell electrocatalyst during the oxygen reduction reaction (ORR). Herein, according to the in‐situ study on nanoscale corrosion kinetics via liquid cell transmission electron microscopy (LC‐TEM) in the authors' previous work, they sequentially designed an optimized nanocube with the protection of more layers on the corners by adjusting the Pt atom distribution on corners and terraces. This modified nanocube (MNC) is much more corrosion resistant in the in‐situ observation. Furthermore, in the practical electrochemical stability testing, the MNC catalyst also showed the best stability performance with the 0.37% and 9.01% loss in specific and mass activity after 30 000 cycles accelerated durability test (ADT). This work also demonstrates that how an in‐situ study can guide the design of desired materials with improved properties and build a bridge between in‐situ study and practical application. Abstract : In situ liquid cell transmission electron microscopy observation is demonstrated as being able to guide the design of highly durable electrocatalysts, which is further verified by in situ corrosion and practical cyclic voltammetry measurements with the loss of 0.37% and 9.01% in specific and mass activities toward the oxygen reduction reaction.